Succinate Supplement Elicited "Pseudohypoxia" Condition to Promote Proliferation, Migration, and Osteogenesis of Periodontal Ligament Cells - Huimin Mao; Andi Yang; Yunhe Zhao; Lang Lei; Houxuan Li (Hindawi Limited, 2020)
Most mesenchymal stem cells reside in a niche of low oxygen tension. Iron-chelating agents such as CoCl2 and deferoxamine have been utilized to mimic hypoxia and promote cell growth. The purpose of the present study was to explore whether a supplement of succinate, a natural metabolite of the tricarboxylic acid (TCA) cycle, can mimic hypoxia condition to promote human periodontal ligament cells (hPDLCs). Culturing hPDLCs in hypoxia condition promoted cell proliferation, migration, and osteogenic differentiation; moreover, hypoxia shifted cell metabolism from oxidative phosphorylation to glycolysis with accumulation of succinate in the cytosol and its release into culture supernatants. The succinate supplement enhanced hPDLC proliferation, migration, and osteogenesis with decreased succinate dehydrogenase (SDH) expression and activity, as well as increased hexokinase 2 (HK2) and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (PFKFB3), suggesting metabolic reprogramming from oxidative phosphorylation to glycolysis in a normal oxygen condition. The succinate supplement in cell cultures promoted intracellular succinate accumulation while stabilizing hypoxia inducible factor-1α (HIF-1α), leading to a state of pseudohypoxia. Moreover, we demonstrate that hypoxia-induced proliferation was G-protein-coupled receptor 91- (GPR91-) dependent, while exogenous succinate-elicited proliferation involved the GPR91-dependent and GPR91-independent pathway. In conclusion, the succinate supplement altered cell metabolism in hPDLCs, induced a pseudohypoxia condition, and enhanced proliferation, migration, and osteogenesis of mesenchymal stem cells in vitro.